Persepsi Guru Terhadap Peran Wali Murid Yang Responsif Dalam Mendukung Keamanan Guru Berdasarkan Undang-Undang Nomor 74 Tahun 2008 - Sri wah yuni; Siti Nur Aisyah; Sofa Ainurrohmah; Thabah Alif Khoirunnisa; Ulfa Umami; Vinka Tiara Pratiwi; Nurul Malika (Muaddib: Jurnal Pendidikan Agama Islam, 2024)
This study aims to explore how teachers assess the role of guardians in creating a safe and supportive environment for them, students, and at school. In the world of education, the role of guardians is very important in creating a conducive work environment for teachers, including providing legal and moral protection. The active involvement of parents in supporting teacher safety can increase teacher confidence, reduce work stress, and create a harmonious relationship between teachers, students, and guardians. However, there are obstacles such as the lack of understanding of parents of students about their rights and obligations and the lack of awareness of the role of the law regulated in the Constitution No. 74 of 2008. This finding is expected to provide input for educational institutions and the government in strengthening the synergy between teachers and guardians.